(untitled) (Revista de Ensino em Artes, Moda e Design, 2020)
This article presents the garments used over the centuries as social indicators and bearers of historical memory, which deserve to be studied and preserved. The research method adopted was based on a relational perspective, with the reading of academic texts on topics relevant to the research, relating them critically, after analyzing the contexts in which they were produced, which provided us with a solid theoretical basis for reflection. The article clarifies that clothing is able to reveal the way social groups behaved, how gender demarcations were established and criteria for distinguishing economic groups. It is in this process of distinction that clothing becomes fashionable, when elites began to use a certain mode of dress as an indicator of wealth, incorporated by all members of the same restricted layer. The article also emphasizes the importance of preventive conservation of this material heritage, so full of immaterialities. Clothing should be understood as guardians of memory, and, as such, should be incorporated into the collections of museums. The article concludes that much more than just “rags”, in the museal environment, fashion and clothing can be studied as document objects by researchers, as well as providing visitors with the unique experience of imagining clothes in their original contexts as carrying life and not as pieces emptied of meaning.